Contrast-enhanced ultrasound (CEUS) identifies perfusion differences between tibial fracture unions and non-unions - Fischer, Christian; Haug, Tabea; Weber, Marc-André; Kauczor, Hans-Ulrich; Bruckner, Thomas; Schmidmaier, Gerhard (Ultraschall in der Medizin, 2020)
To assess the value of CEUS in the evaluation of tibial fracture perfusion and its ability to differentiate between physiologic and abnormal fracture healing.
Online veröffentlicht: 6. August, 2018
Gesehen am 01.04.2020